Energy requirements in mammalian oogenesis - Arhin, Samuel Kofi; Lu, Jieqiang; Xi, Haitao; Jin, Xingliang (Cellular and Molecular Biology, 2018)
Oogenesis is a lengthy, multi-step process occurring in mammals yielding single or multiple oocytes capable of being fertilized upon interaction with male gametes. The overall process is highly complex in nature, starting in the primordial follicles, and its ultimate completion is preceded by the meiotic cycle. There are two major phases in oogenesis: the growth phase, followed by a maturation phase that requires relatively less time. Both phases require energy for the various metabolic processes of the oocytes. The energy requirements and the timing of maturation vary significantly among mammalian species. This review describes the variations in the mammalian oocytes development and their energy requirements. It covers the types of mitochondria, the distribution of their changes, and the metabolic processes occurring during the oogenesis in different mammalian species. Oocyte abnormalities associated with glucose deficiency in mammals are discussed, along with the role of fat and protein as alternative energy substrates. The review concludes with recommendations for future studies on oogenesis in mammalian species in the context of energy requirements.